2017
DOI: 10.3390/molecules22010123
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Antihypertensive Peptides Derived from Adlay (Coix larchryma-jobi L. var. ma-yuen Stapf) Glutelin

Abstract: Our previous studies have shown that Coix glutelin pepsin hydrolysate can effectively inhibit angiotensin converting enzyme (ACE) activity in vitro. The main purpose of this study was to obtain potent anti-hypertensive peptides from Coix glutelin. The Coix glutelin hydrolysates (CGH) were prepared by pepsin catalysis and further separated by an ultrafitration (UF) system, gel filtration chromatography (GFC) and reversed-phase high performance liquid chromatography (RP-HPLC). As a result, the sub-fraction F5-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
1
19
0
1
Order By: Relevance
“…On the contrary, when the hydrolysate was orally administered (by using feeding tubes), a significant effect was seen after 3 h. Similarly, Matsui et al [ 19 ] reported that an antihypertensive peptide and captopril could decrease the systolic blood pressure in spontaneous hypertensive rats after 3 h of oral administration (by using feeding tubes). Others have reported that the highest antihypertensive effect of the antihypertensive peptide GAAGGAF from Coix lachryma-jobi occurs after 4 h to 6 h of administration, and the effect remains until 7 h post-supplementation [ 20 ]. Our findings are in line with the previous studies and confirm that an optimized amaranth hydrolysate has a hypotensive effect in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, when the hydrolysate was orally administered (by using feeding tubes), a significant effect was seen after 3 h. Similarly, Matsui et al [ 19 ] reported that an antihypertensive peptide and captopril could decrease the systolic blood pressure in spontaneous hypertensive rats after 3 h of oral administration (by using feeding tubes). Others have reported that the highest antihypertensive effect of the antihypertensive peptide GAAGGAF from Coix lachryma-jobi occurs after 4 h to 6 h of administration, and the effect remains until 7 h post-supplementation [ 20 ]. Our findings are in line with the previous studies and confirm that an optimized amaranth hydrolysate has a hypotensive effect in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…ma-yuen Stapf ) Glutelin”. Change in Main Body Paragraphs There are three errors in this article [ 1 ]: Section 2.6. The ACE Inhibitory Activity of GAAGGAF In Vitro should be corrected to 2.6.…”
mentioning
confidence: 99%
“…Li et al . () had established that adlay glutelin hydrolysate can effectively inhibit ACE activity in vitro . The promoted ACE inhibitory activity might be attributed to the release of bioactive peptides during adlay germination.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study also revealed that germination can improve the ACE inhibitory activity of legume samples (Mamilla & Mishra, 2017). Li et al (2017) had established that adlay glutelin hydrolysate can effectively inhibit ACE activity in vitro. The promoted ACE inhibitory activity might be attributed to the release of bioactive peptides during adlay germination.…”
Section: In Vitro Inhibition Of Ace Tyrosinase and Xanthine Oxidasementioning
confidence: 95%